2021
DOI: 10.17509/jomsign.v5i2.35063
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance in Madrasah Students Based on Religious Organization Affiliates

Abstract: This article contains a description of tolerance in students of Madrasah Aliyah Negeri 1 Cimahi. The method used is a descriptive method with a quantitative approach. Data collection using tolerance instruments. The research sample consisted of 120 students of Madrasah Aliyah Negeri 1 Cimahi and 64 students identified who were affiliated with Nahdlatul Ulama and Muhammadiyah religious organizations. The results of this study are first that the tolerance of students at Madrasah Aliyah Negeri 1 Cimahi is in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Students with low equality perception have weak relationships. In other words, an environment that welcomes connection between diverse individuals positively improves group and lowers the group identification level, primarily on individuals supporting equality (Septian & Budiman, 2021). Equality among students encourages a positive learning climate, along with positive engagement orientation with outside groups (Rabinowitz, Wittig, von Braun, Franke, & Zander-Music, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students with low equality perception have weak relationships. In other words, an environment that welcomes connection between diverse individuals positively improves group and lowers the group identification level, primarily on individuals supporting equality (Septian & Budiman, 2021). Equality among students encourages a positive learning climate, along with positive engagement orientation with outside groups (Rabinowitz, Wittig, von Braun, Franke, & Zander-Music, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Equality should be given to all people, including people with different educational backgrounds, cultures, economic statuses, and ethnicity (Guinote, Cotzia, Sandhu, & Siwa, 2015). Besides, a study reported that prejudice among students could be reduced by developing equality and introducing positive behaviors toward different groups (Septian & Budiman, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite Indonesia getting international recognition for its diversity and efforts to create tolerance of religion (Johan, 2020), the results of previous studies in the Islamic education context were not always in line. The studies addressed on multicultural of Muslim students in rural and urban areas (Wibowo, 2018), attitude differences between public Islamic and public university students (Rifa'i, 2019), tolerance of Muslim pre-service teachers (Mulya et al, 2021), and tolerance among Islamic high school students (Septian & Budiman, 2021) proved the different perspectives of understanding and practicing multicultural. For this finding, Zarbaliyev (2017) signaled that, at any time, ethnic conflicts might appear.…”
Section: The Rational Of Current Studymentioning
confidence: 99%